Kesepian Remaja Pada Masa Pandemi COVID-19 - Dony Darma Sagita; Dede Hermawan (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2020)
The COVID-19 pandemic is a complex problem in the life of Indonesian society today, including aspects of individual personality. The purpose of this study was to empirically examine the level of adolescent loneliness during the COVID-19 pandemic. This study used quantitative method research with a descriptive approach. The sample were 300 adolescents that selected by convenience sampling technique. The results showed that the level of loneliness of adolescents during the COVID-19 pandemic was in a quite high category with a proportion of 43%, 10% in high category, and 1,7% in very high category. It means the adolescent need to be more attention so that teenagers can lead a normal life in their daily lives.